PENGARUH PROSEDUR ANALITIS DAN PEMAHAMAN RISIKO AUDIT TERHADAP PENGEMBANGAN PROGRAM AUDIT (Hasil studi pada beberapa KAP di Bandung) - Deddy Supardi (Bina Ekonomi, 2008)
The aim of this research is to investigate the influence of analytical procedures and audit risk toward the development of audit program and relationship between analytical procedures and audit risk.The audit program is the key to successful in auditing pertormance inaccordance with auditing standards. Method of data analysis used to identity research objectives are correlation and path analysis. The results show that have correlation significant between analytical procedures and audit risk and influence significant analytical procedures and audit risk to audit program